Isolasi Senyawa Utama Daun Setebal (Glochidion superbum) dan Uji Aktivitas Antioksidan dengan Metode DPPH (1,1-difenil-2-pikrilhidrazil) - Rachel Bintang; Ghalib Syukrillah Syahputra; Sri Budiasih (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Thick leaf (Glochidion superbum) is a medicinal plant traditionally utilized by the community of East Panjang Island for the treatment of wounds, pain, and ulcers. This research was conducted to isolate the major compounds present in the ethyl acetate fraction of thick leaf and to assess its antioxidant activity using the DPPH method. The plant leaves were first cleaned, dried, and powdered, followed by maceration extraction using methanol, which resulted in an extract yield of 16.42%. The crude extract was fractionated by column chromatography using EtOAc and MeOH eluents with ratios of 9:1 (K1), 4:1 (K2), 1:4 (K3), and 1:9 (K4). UV–Vis spectrophotometric analysis showed an absorption peak at 288 nm, indicating the presence of phenolic compounds, identified as ferulic acid. Antioxidant testing using the DPPH method showed IC₅₀ values for fractions K1, K2, K3, and K4 of 12.981, 5.159, 9.658, and 10.971 µg/mL, respectively, with vitamin C as a positive control (3.563 µg/mL). Fraction K2 showed the strongest antioxidant activity. These results indicate that thick leaf contains ferulic acid with very strong antioxidant activity and has potential as a natural antioxidant source.